BUSINESS ENGLISH COURSEBOOK DESIGN FOR ECONOMICS AND BUSINESS STUDENTS USING ADDIE - Paramita, Paulina Erawati; Dudy Effendy (UNIVERSITAS SERAMBI MEKKAH, 2024)
This article explores the development of a Business English coursebook for economics and business students using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), as presented by Paulina Erawati Paramita from Widya Dharma Pontianak University at the 6th Annual International Conference of African ELTA 2022. It details each stage of the ADDIE process, focusing on tailoring the coursebook to the specific needs of this target audience. Through needs analysis, the article identifies challenges and knowledge gaps faced by economics and business students in English communication. Subsequently, it outlines the coursebook's design, including learning objectives, content selection, and methodology. Development delves into the creation of engaging and relevant learning activities, while implementation explores pedagogical strategies and teacher support. Finally, the article emphasizes the importance of continuous evaluation through formative and summative assessments to ensure the coursebook's effectiveness. It is expected that Conference participants will actively engage in developing and designing coursebooks tailored to their specific needs.